2018
DOI: 10.1016/j.nicl.2017.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Priming production: Neural evidence for enhanced automatic semantic activity preceding language production in schizophrenia

Abstract: IntroductionLexico-semantic disturbances are considered central to schizophrenia. Clinically, their clearest manifestation is in language production. However, most studies probing their underlying mechanisms have used comprehension or categorization tasks. Here, we probed automatic semantic activity prior to language production in schizophrenia using event-related potentials (ERPs).Methods19 people with schizophrenia and 16 demographically-matched healthy controls named target pictures that were very quickly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…Recent work in computational linguistics have suggested considerable potential for language as a biomarker in schizophrenia, as automated linguistic measures can predict symptoms of schizophrenia including FTD (Elvevåg et al 2010;Bedi et al 2015;Holshausen et al 2014). Experimental psycholinguistic studies have also revealed numerous language processing anomalies in schizophrenia, largely in comprehension/perception (Titone et al 2007;Kuperberg 2010;Kuperberg et al 2017; but see Kuperberg et al 2018, for a recent study of semantic priming in a naming task), and in part specific to FTD (Kuperberg et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in computational linguistics have suggested considerable potential for language as a biomarker in schizophrenia, as automated linguistic measures can predict symptoms of schizophrenia including FTD (Elvevåg et al 2010;Bedi et al 2015;Holshausen et al 2014). Experimental psycholinguistic studies have also revealed numerous language processing anomalies in schizophrenia, largely in comprehension/perception (Titone et al 2007;Kuperberg 2010;Kuperberg et al 2017; but see Kuperberg et al 2018, for a recent study of semantic priming in a naming task), and in part specific to FTD (Kuperberg et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For ERP data analysis, a representative sub-array of nine channels was used (Blackford, Holcomb, Grainger & Kuperberg, 2012; Chauncey, Grainger & Holcomb, 2008; Grainger, Kiyonaga & Holcomb, 2006; Kuperberg, Delaney-Busch, Fanucci & Blackford, 2018). As Blackford and colleagues (2012) mentioned, following this design, a single analysis of variance (ANOVA) can be used for each time window analysis; and, hence, this electrode selection is a good meeting point between the use of a simple design and the correct description of the overall distribution of the effects.…”
Section: Methodsmentioning
confidence: 99%
“…As outlined in the Introduction, an enhanced automatic indirect priming effect in schizophrenia could, in theory, result either from an unconstrained (or disinhibited) spread of activity across semantic memory (e.g. Manschreck et al, 1988), or from noisier lexical representations --that is, looser (less finely-tuned) mappings/connections between representations of word-form and semantic features (Brown and Kuperberg, 2015;Kuperberg et al, 2018a), see Fig. 1.…”
Section: Mechanism Of the Enhanced Indirect Automatic Priming Effect mentioning
confidence: 99%
“…1B. It holds that these formmeaning (lexical) mappings are weaker and less finely-tuned in people with schizophrenia than in healthy adults (Brown and Kuperberg, 2015;Kuperberg et al, 2018a). For example, in healthy controls, the lexical representation, BELL, encodes tight mappings between the semantic features, < bell > , and the specific word-form, b-e-l-l.…”
Section: Two Possible Mechanisms Of Increased Automatic Indirect Primmentioning
confidence: 99%